Biological factors affecting variability of persistent pollutant levels in cetaceans - Aguilar, A.; Borrell, A.; Pastor, T. (J. Cetacean Res. Manage., 1999)
The main biological factors responsible for the variability of pollutant concentrations in cetaceans are reviewed. Diet is significant because many pollutants are concentrated through food webs. This explains most interspecific differences in pollutant levels and it may also contribute to variation among populations of the same species or even among different components of the same population when diet is subject to age-related or sex-related variations. The effect of body size is complex. Excretion rate and activity of detoxifying enzymes decrease as body weight increases, processes which would lead to higher pollutant concentrations in large animals. In contrast, a high metabolic rate, which is inversely correlated to body size, is associated with high pollutant concentrations. These opposing effects usually result in higher residue levels in smaller individuals. Body composition affects the contribution of each body compartment to the overall pollutant load. Therefore, the body load of lipophilic pollutants will strongly depend on the relative mass of blubber, a variable that shows a threefold variation among cetacean species or, in seasonal feeders, among individuals. Nutritive condition also affects the dynamics of lipophilic pollutants. Lipid mobilisation results in an increase in residue levels, but this variation is not as large as a purely concentrative model would suggest because of enhancement of detoxification processes following a rise in tissue pollutant concentrations. Disease affects pollutant levels in different ways: impoverishing nutritive condition; altering normal physiological functions; and depressing reproduction therefore reducing reproductive transfer in females. The combined result of these processes is usually an increase in pollutant levels in diseased individuals. The concentration of lipophilic pollutants normally increases with age in males because input exceeds the ability of the organism to excrete pollutants. Variable proportions of the pollutant load are transferred to offspring during gestation and lactation, for which reason tissue concentrations in females decrease or stabilise, thus producing lower residue levels than in males. However, because not all compounds are transferred at the same rate, their relative abundance varies with age and sex. Intensity of reproductive transfer is also associated with the reproductive traits of the species, particularly the length of lactation. With the exception of zinc, concentrations of heavy metals increase with age in both sexes but, by contrast with lipophilic pollutants, concentrations in females are similar or higher than in males. The significance of these factors of variation should be taken into account when designing sampling methodology, comparing sample groups, or evaluating toxicological impact.